SINGLE CUSTOMS TARIFF REGULATIONIN THE CUSTOMS UNION OF THE REPUBLIC OF BELARUS,REPUBLIC OF KAZAKHSTAN AND THE RUSSIAN FEDERATION (Journal of actual problems of jurisprudence, 2019)
This article provides an overview and legal aspects of making organ of the Eurasian Economic Community (EEC) concerningthe functioning of the Customs Union.